Pengembangan Buku Ajar Fisika Berbasis Problem Based Learning pada Materi Elastisitas dan Hukum Hooke - Dwi Putri Harefa; Ovilia Putri Utami Gumay (LP4MK STKIP PGRI Lubuklinggau, 2021)
This study aims to develop a Problem Based Learning Physics Textbook on the subject of Elasticity and Hooke's Law that is valid, and practical. The problems in this study are 1) How is the quality of Physics textbooks based on Problem Based Learning if viewed in terms of validity, and practicality, in class XI SMA Negeri 2 Lubuklinggau? 2) How to design and develop a Problem Based Learning-based physics textbook that meets the objectives of validity, and practicality, in class XI of SMA Negeri 2 Lubuklinggau?. The subjects in this study were class XI MIA 2 which consisted of 9 students who were taken by purposive sampling technique. The development model in this study refers to the development model of Sugiyono which consists of 1.Potential and problems, 2.Data collection, 3.Product design, 4.Design validation, 5.Design revision, 6.Product trial, 7.Product revision, 8.Usage trial, 9.Product revision, 10.Mass production. But in this research, only used 9 stages of development. Data was collected by using a student response questionnaire technique. And validation consists of 3 expert validations, material validation with an assessment of 42 in the very good category, language validation with an assessment of 18 in the good category, and media validation with an assessment of 28 in the good category. The validation carried out got results with an assessment of 88 in the good category. Student responses to the physics module based on Problem Based Learning with an assessment of 330 in the very good category. So it can be said that the Problem Based Learning-based physics textbook that has been developed is valid, and practical.